The jungle book - Jungle book (Motion picture : 1967); Clemmons, Larry 1906-1988; Disney, Walt 1901-1966; Walt Disney Pictures; Walt Disney Productions (Burbank, CA Walt Disney Home Entertainment Distributed by Buena Vista Home Entertainment, 2007)
Mowgli is a boy who has been raised by wolves in the Indian jungle. When the wolves hear that the fierce tiger, Shere Kahn, is nearby, they decide to send Mowgli to a local "man tribe." On his way to the village, Mowgli meets and befriends many jungle animals
Based on the novel by Rudyard Kipling
1
Keywords: Friendship -- Juvenile films; Mowgli (Fictitious character) -- Drama; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs